Managing, making sense of and finding meaning in advanced illness: a qualitative exploration of the coping and wellbeing experiences of patients with lung cancer. Issue 8 (16th October 2017) - Harrop, Emily; Noble, Simon; Edwards, Michelle; Sivell, Stephanie; Moore, Barbara; Nelson, Annmarie
Abstract: Coping plays an essential role in maintaining the wellbeing of patients with cancer. A number of different coping responses and strategies have been identified in the literature. The value and relevance of meaning based coping theory has also been emphasised, including Antonovosky's Sense of Coherence (SoC) theory. Ten patients with advanced lung cancer were interviewed up to three times. A total of twenty in depth interviews were carried out, fully transcribed and data were analysed following a methodology of Interpretative Phenomenological Analysis. Three broad domains were identified to categorise the core life concerns of participants; making sense of and managing one's illness; maintaining daily life and relationships and confronting the future. Within these domains multiple coping themes are identified, which to varying degrees help to maintain patient wellbeing and quality of life. This article considers the relevance of SoC theory for understanding the coping experiences of patients with advanced cancer, and identifies resources and factors likely to support patient coping, with implications for health and social care services.